Respuesta :

s1m1

Answer:

x= -3, y= 13

Step-by-step explanation:

The idea is that x and y in both equations are the same numbers and that the equations are like rules that need to be followed both in the same time.

We take the y from one equation and use it in the other equation because is the same y .

3x+y =4 , subtract 3x from both sides

y=  -3x+4

2x+y =7 , substitute y with the y = -3x+4 from the first equation

2x -3x+4 = 7, subtract 4 from both sides

2x-3x = 7-4, combine like terms

-x = 3  so x = -3

We know that x= -3 so we can substitute it in y= -3x+4 to find y

y=  -3x+4

y= -3 (-3) +4

y= 9+4 = 13

y= 13